An Evaluation of Objectivity and Competence of Internal Audit Departments in Sudanese Government Units - Obeid, Obeid Ahmed; Abdelnur, Amna (International Journal of Economics and Financial Issues, 2018)
The purpose of this study is to evaluate objectivity and competence of internal audit departments in Sudanese government units across a sample of internal auditors of government units and external auditors responsible for auditing. 101 questionnaires were completed and used for the purpose of analysis to test six hypotheses. (July – August 2017). The study results revealed that internal and external auditors’ perceptions of objectivity were affected by internal audit departments reporting level as the majority of internal audit departments reporting level was the manager of the unit and influences of appointing and removing internal audit directors. Regarding competence, it was found to be dissatisfactory due to rare opportunities of training in auditing and internal auditing, inexperienced staff and high turnover of internal auditors. However, the results of this paper will be of concern to government units in their attempt to improve objectivity and competence of internal audit functions. Keywords: objectivity, competence, government units, internal auditing JEL Classifications: G3, G34